Research in Iran: Look on the Bright Side - L Kashani; Sh Akhondzadeh (Institue of Medicinal Plants, ACECR, 2017)
Regarding to Dr. Richard Stone's report entitled "Iran, a shady market for papers flourishes" published in Science 15th September 2016.  There are several points in the articles that require particular attention. The report, although presents some truth, lacks depth and balance on a problem that is not unique to Iran. To begin to understand this, perhaps one needs to remind the author that Iran's scientific infrastructure took a huge blow during 8 years of Saddam Hossein's Imposed war. This resulted in massive reduction of scientific output. For example, based on Web of Science, scientific publications from Iran before the war was twice as many as that of Turkey, which has similar population and economy, but during the war it dropped to one tenth of Turkey. Iran managed to revive its scientific infrastructure over the last 25 years to the extent that in 2011 Iran had the faster growing scientific production in the world [1]. Industry followed similar suit. For example, Iran now produces 90% of all pharmaceutical drugs, health care quality improved so that the average life expectancy increased by 10 years, number of governmental universities increased remarkably and so on. While we had to import many foreign doctors from India, Bangladesh and Pakistan to provide health care in remote areas, today Iran is totally self-sufficient for training doctors and provides quality health care even in remote areas. None of these were achieved by buying thesis in front of Tehran University.